Mechanism design and analysis of six-bar linkage structure for vegetable transplanting - Ngamvilaikorn, Tawee; Chooprasird, Kummun (Agriculture and Natural Resources, 2022)
This study presents a new vegetable farming mechanism with a six-bar linkage structure installed on a watering crane so that this mechanism can be adjusted for the spacing between plants by changing the anchor points of link 5 without any adjustment of the angular speed of the input cranks. This is beneficial in terms of convenience, simplicity and low cost compared to other mechanisms that mainly need adjustment to the angular speed of the input cranks that is complicated and expensive. In addition, this new mechanism provides adjustment for three planting distances (200 mm, 250 mm, 300 mm). Kinematics were analyzed to determine the speed of the planting duckbill, the crane, the anchor points of link 5, planting distances and the zero-speed of the planting duckbills. The results showed that transplanting with the six-bar mechanism installed in the crane produced the planting distances as required and the plants had vertically straight stems and were healthy and well grown.